Stat1 is an inducible transcriptional repressor of neural stem cells self-renewal program during neuroinflammation - Imitola, Jaime; Hollingsworth, Ethan W.; Watanabe, Fumihiro; Olah, Marta; Elyaman, Wassim; Starossom, Sarah; Kivisäkk, Pia; Khoury, Samia J. (Frontiers in Cellular Neuroscience, 2023)
A central issue in regenerative medicine is understanding the mechanisms that regulate the self-renewal of endogenous stem cells in response to injury and disease. Interferons increase hematopoietic stem cells during infection by activating STAT1, but the mechanisms by which STAT1 regulates intrinsic programs in neural stem cells (NSCs) during neuroinflammation is less known. Here we explored the role of STAT1 on NSC self-renewal. We show that overexpressing Stat1 in NSCs derived from the subventricular zone (SVZ) decreases NSC self-renewal capacity while Stat1 deletion increases NSC self-renewal, neurogenesis, and oligodendrogenesis in isolated NSCs. Importantly, we find upregulation of STAT1 in NSCs in a mouse model of multiple sclerosis (MS) and an increase in pathological T cells expressing IFN-γ rather than interleukin 17 (IL-17) in the cerebrospinal fluid of affected mice. We find IFN-γ is superior to IL-17 in reducing proliferation and precipitating an abnormal NSC phenotype featuring increased STAT1 phosphorylation and Stat1 and p16ink4a gene expression. Notably, Stat1–/– NSCs were resistant to the effect of IFN-γ. Lastly, we identified a Stat1-dependent gene expression profile associated with an increase in the Sox9 transcription factor, a regulator of self-renewal. Stat1 binds and transcriptionally represses Sox9 in a transcriptional luciferase assay. We conclude that Stat1 serves as an inducible checkpoint for NSC self-renewal that is upregulated during chronic brain inflammation leading to decreased self-renewal. As such, Stat1 may be a potential target to modulate for next generation therapies to prevent progression and loss of repair function in NSCs/neural progenitors in MS.